مبدأ الحيطة في المسؤولية المدنية وفقا للتشريع البيئي - إلياس بن جديد (My University, 2018)
Summary: This note addresses one of the most recent principles first formulated in principle 15 of the 1992 Rio Declaration: "Where there are threats of serious or irreversible damage, and lack of full scientific certainty cannot be justified to postpone the adoption of effective measures to prevent environmental degradation" The principle of caution was adopted by Algerian legislation in Act No. 03-10 on the protection of the environment in the context of sustainable development. It contributes to the development of civil liability to take precautionary measures to protect the environment. ......................... الملخص : تعالج هذه المذكرة مبدأ من أهم المبادئ حديثة النشأة الذي صيغة لأول مرة في المبدأ 15 لإعلان ريو سنة 1992 : " عندما تكون هناك تهديدات بوقوع أضرار جسيمة أو لا رجعة فيها ، و الإفتقار إلى البقين العلمي الكامل لا يمكن أن يكون مبررا لتأجيل إعتماد تدابير فعالة لمنع التدهور البيئي " و مبدأ الحيطة تبناه المشرع الجزائري في القانون 03-10 المتعلق بحماية البيئة في إطار التنمية المستدامة . و هو يساهم في تطوير المسؤولية المدنية إلتخاذ التدابير اإلحتياطية لحماية البيئة . ........................ Résumé : Cette note traite de l’un des principes les plus récents formulés pour la première fois dans le principe 15 de la Déclaration de Rio de 1992 : "Lorsqu’il existe des menaces de dommages graves ou irréversibles, et que le manque de certitude scientifique ne peut être justifié pour retarder l’adoption de mesures efficaces pour prévenir la dégradation de l’environnement" Le principe de prudence a été adopté par la législation algérienne dans la loi no 03-10 sur la protection de l’environnement dans le contexte du développement durable. Elle contribue au développement de la responsabilité civile de prendre des mesures de précaution pour protéger l’environnement.